Abnormal vibration analysis of metro axlebox based on vehicle-track coupling system. (January 2023) - Shi, Yixuan; Dai, Huanyun; Wang, Qunsheng; Li, Dadi; Peng, Xinyu
In the operation process of metro, abnormal vibration occurs at the axlebox, and causing structure damage on some components, so the dynamic test was carried out. The result shows that the abnormal vertical vibration about 80–120 Hz is the direct cause in the vehicle operation, and it relates to the type of track bed. According to the track and vehicle, two finite element vertical models of vehicle-track coupling system were established. It determines that the first order vertical bending mode of rail in the coupling system is the excitation source of the abnormal vibration through frequency analysis. And this mode is mainly related to the vertical stiffness of fastener and rubber cushion under short sleeper, which will increase with these stiffness values. Finally, through actual stiffness measurement, it sees that the fastener vertical stiffness values in ordinary track section are mostly reduced to the frequency range corresponding to the first vertical bending mode of rail in the coupling system, which is the cause of abnormal vibration. Therefore, by adjusting the fastener vertical stiffness or adopting the track type to be a damping track bed, the impact of vibration near 80–120 Hz can be reduced, so as to avoid the structural failure of vehicle components and ensure the operation safety of metro vehicles.